The Influence Of Social Presence Through The Web Interface Towards Online Shopping Attitude Of Undergraduate Students In Umk (Kampus Kota), Pengkalan Chepa - Eng, Wen Qi; Mohd Arif, Mohamad Amiruddin; Thayananthan, Nalini; Hamiruddin, Nur Hidayah (2015)
This paper mainly explained about the online shopping attitude of undergraduate student in UMK Kampus Kota. There have several factors such as perceived usefulness, trust and enjoyment that influence the student’s buying attitude were analyzed. The objective of this study is to examine the relationship between perceived usefulness, trust, enjoyment toward online shopping attitude. Total sample size in this research is 346 respondents who were selected are undergraduate students in UMK Kampus Kota. The average mean for perceived usefulness, trust and enjoyment indicates that respondent have strongly agreed that all the factors were affect the online shopping attitude. The result Pearson correlation in this research was indicates the positive relationship from perceived usefulness, enjoyment and trust toward online shopping attitude. Among the variables, perceived usefulness was proven to be the most influenced variable on online shopping attitude followed by enjoyment and trust.